PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIa SMP AN NAMIROH PEKANBARU - Hasanah, Ajroni; Anggraini, Rini Dian; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was based on the low student’s achievement in mathematics in grade VIIa of SMP An Namiroh Pekanbaru. From data of daily students was obtained the percentage of students who got the Mastery Minimum Criteria were 43,3% for main subject Integers and 13,3% for subject Algebra. This research is a class action research. This research aims to improve the learning process and improve learning result in mathematics by implementation of cooperative learning Think Pair Square (TPS) approach. The subject of this research were the students in the class VIIa of SMP An Namiroh Pekanbaru at the even semester of academic year 2016/2017 that consist of 14 boys and 15 girls. The instruments of data collection in this research were observation sheets and student’s mathematic tests. The observation sheets were analyzed in desciptive narative to see the process of activities learning process that the implementation wasn’t based on plan that was made so it can be arranged the improvemen plan for second cycles while the student’s mathematic tests were analyzed in statistic desciptive. The result of this research showed an improvement of learning process and student’s achievement of learning mathematic prior to the action on the first and second cycles. The students have be seriously in doing students worksheets by develop their own capability and every member of group took an active part in doing students worksheets. The students also were confident if being showed to do the presentation and being more active in giving idea for group who did the presentation. From the analysis of getting the Mastery Minimum Criteria showed an improvement student’s achievement from the basic score with percentage 34,5% to the first test with percentage 41,4% to second test with percentage 54%. Based on the result of this research could be concluded that the implementation of cooperative learning Think Pair Square (TPS) Approach can improve the learning process and improve the student’s achievement of learning mathematic in grade VIIa of SMP An Namiroh Pekanbaru at the even semester of academic year 2016/2017.Key Words : Students Math Achievement, Cooperative Learning Think Pair Square Approach, Clasroom Action Research.